Smart Promotion: Artificial Intelligence Training for Designing Digital Promotional Materials for UP2K PKK MSME Entrepreneurs in Punden Rejo Village - Tantri Octora Dwi Syah Putri; Esther Praja Anggriany Panggabean; Mas Intan Purba; Isna Asdiani Nasution; Faisal Akbar; Yan Raja David Hamonangan Damanik; Nurul Wardani Lubis (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Digital transformation requires Micro, Small, and Medium Enterprises (MSMEs) to produce attractive and professional promotional materials to capture the attention of digital consumers. However, limited knowledge of editing and graphic design remains a major challenge, particularly for members of the Family Income Improvement Program (UP2K PKK). This community service program aimed to enhance the capacity of MSMEs supported by UP2K PKK in Punden Rejo Village, Tanjung Morawa District, Deli Serdang Regency, to utilize generative Artificial Intelligence (AI) technology for designing digital promotional materials, with a particular emphasis on developing effective prompt engineering skills. The program employed a training approach consisting of demonstrations and hands-on mentoring for 15 participants. The activities included education on the importance of promotion for business sustainability, an introduction to prompt concepts in AI tools, and practical sessions on creating digital promotional materials using AI applications on smartphones. The results showed that participants were able to understand and formulate simple prompts by specifying product types, visual styles, desired moods, and color schemes, enabling them to independently produce more engaging digital promotional materials. Participants demonstrated high enthusiasm through active discussions and by establishing a WhatsApp group as a platform for continuous mentoring, where they shared and received feedback on their promotional content. The integration of promotional strategy education with practical training in the use of generative AI proved effective in increasing MSMEs' confidence in producing promotional materials easily, affordably, and efficiently without requiring advanced graphic design skills. This initiative contributes to strengthening the competitiveness of MSMEs in the digital economy.